PERBANDINGAN METODE THINK-PAIR- SHARE DENGAN METODE CERAMAH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN INSTALASI PERANGKAT JARINGAN LAN JURUSAN TKJ KELAS I SMK N 5 PADANG - Sari Utami; Nurindah Dwiyani; Legiman Slamet (Universitas Negeri Padang, 2014)
The learning method in computer engineering and network at SMK N 5 Padang apply the direct learning method that have appreciation character and apply the speech method which is appropriate with the lesson,however, the student doesn’t have great motivation to follow the lesson and the lesson result is still under school grades standard.Because of that, it needs a learning model to make the student more active along with the increase of motivation and the student learning result in learning process. Based on the indication above, it conclude that the research question in this thesis is Is there any positive influence and significant toward the student learning result by using TPS method.The hypothesis of this research is there is the influence of TPS method toward the student learning result.This research uses the experiment phenomenological to see the influence of the student learning result by using TPS method and speech method.The population of the research is the student in first grade at SMKN 5 Padang 2013/2014 and the determining sample method is the purposive sampling with the result that the sample is the 1TKJ1A class by using speech method as the control class and 1TKJ1B by using TPS method as experiment group.Based on the research result, it seen that there is a comparison between the effect of stdent learning result experiment class and control class with 49,29% by using TPS method and 33,33% by using speech method.From the hypothesis test it is got that t count value is outside of Ho acceptance.It is mean that in the real situation the research shows that there is an influence of learning result and it is significant between TPS method and speech method in the lan network set installation lesson grade 1at SMK N 5 Padang. Keywords: Comparison, think pair share, speaking, learning result.